The Role Of The Prosecutor's Office And The BPK In The Process Of Returning State Losses Between Dominus Litis And Justice - Sitompul, Ariman (Legalpreneur Journal, 2026)
This study examines the role of the prosecutor's office and the Supreme Audit Agency (BPK) in the process of returning state losses due to corruption, especially in relation to the dominus litis principle and the dimension of Justice. The method used is juridical normative approach to legislation and conceptual through the study of literature (library research). The results showed that the relationship of authority between the prosecutor's office and the BPK is complementary but has not been coordinated systematically, resulting in normative gaps that weaken the effectiveness of state asset recovery. The dominus litis principle that gives prosecutorial authority to prosecutors is in practice limited by the principle of functional differentiation that separates investigation and prosecution. The restorative justice approach and the establishment of an Asset Recovery Agency is a positive institutional breakthrough, but requires strengthening interagency coordination regulations so that the goal of returning state losses can be optimally achieved. This study concludes the need for special regulations that regulate formal coordination between the prosecutor's office and the BPK as the foundation for fair and measurable recovery of State losses.